Factors Effecting Consumers Buying Interest toward Online Frozen Food during the Covid 19 Pandemic in Padang City - Rona Fahreza; Syafrizal Syafrizal (Institute of Computer Science (IOCS), 2021)
This research aimed to determine the effect of subjective norms, the effect of behavioral control, the effect of health conscious and the effect of perceived price on buying interest during the COVID-19 pandemic in the city of Padang. The population in this research were the consumers in Padang city. While the sampling method used was purposive sampling method, which 21 samples were multiplied by 5 so that the number of samples in this research was 105 respondents. Data analysis was carried out using the SmartPLS. The results showed that perceived price, health conscious and informational influence had a significant effect on buying interest.